2022
DOI: 10.3390/polym14101944
|View full text |Cite
|
Sign up to set email alerts
|

Ceramifiable Silicone Rubber Composites with Enhanced Self-Supporting and Ceramifiable Properties

Abstract: Ceramifiable silicone rubber (SR) composites with excellent self-supporting properties and ceramifiable properties were prepared by incorporating silicate glass frits (SGFs) and sodium tripolyphosphate (STPP) into the SR. Ceramic residues were obtained by firing ceramifiable SR composites at 700, 850, and 1000 °C for 30 min. The bending angles of the composites were tested for evaluating the self-supporting property. To evaluate the ceramifiable properties of the ceramifiable SR composite, flexural strength, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Recently, ceramizable silicone rubbers (CSR) were developed as a novelty flameresistant insulating material, and are composed of a silicone rubber matrix, fluxing agent, inorganic filler, and vulcanizing agent, exhibiting excellent thermal, electrical, and mechanical properties [11][12][13][14]. During the high-temperature combustion process, CSR can transform into robust ceramic materials on the surface of power cables to prevent the development of flames [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ceramizable silicone rubbers (CSR) were developed as a novelty flameresistant insulating material, and are composed of a silicone rubber matrix, fluxing agent, inorganic filler, and vulcanizing agent, exhibiting excellent thermal, electrical, and mechanical properties [11][12][13][14]. During the high-temperature combustion process, CSR can transform into robust ceramic materials on the surface of power cables to prevent the development of flames [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…After sintering, the flexural strength of silicone rubber is generally high. [17][18][19] What is more some special substances, including platinum, [20][21][22] iron oxide, 23 and boron, 24 can significantly promote ceramification of silicone rubber. In addition to silicone rubber, other special polymers containing boron and silicon are also easy to ceramification.…”
Section: Introductionmentioning
confidence: 99%
“…It can be easily to ceramification with some inorganic materials. After sintering, the flexural strength of silicone rubber is generally high 17–19 . What is more some special substances, including platinum, 20–22 iron oxide, 23 and boron, 24 can significantly promote ceramification of silicone rubber.…”
Section: Introductionmentioning
confidence: 99%
“…10 The addition of the phosphorus-based flame-retardant sodium tripolyphosphate (STPP) to silicone rubber increases the relative content of the crystalline phase by about 25%, which can enhance the shape stability and self-supporting properties of the composites at high temperatures. 11 The porous ceramic silicone rubber (PCSR) composites in our study similarly incorporated GP, aluminum hydroxide and phosphorus-nitrogen flame retardants to enhance the composites' flame retardancy and the robustness of the carbon layer structure. However, few studies have been reported on the effect of matrix portion in porcelainised silicone rubber on mechanical and fire resistance properties, especially on tensile shear strength at different temperatures for a wide range of substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of flame retardants is the most effective way to improve the flame retardancy of silicone rubber 10 . The addition of the phosphorus‐based flame‐retardant sodium tripolyphosphate (STPP) to silicone rubber increases the relative content of the crystalline phase by about 25%, which can enhance the shape stability and self‐supporting properties of the composites at high temperatures 11 . The porous ceramic silicone rubber (PCSR) composites in our study similarly incorporated GP, aluminum hydroxide and phosphorus‐nitrogen flame retardants to enhance the composites' flame retardancy and the robustness of the carbon layer structure.…”
Section: Introductionmentioning
confidence: 99%